Studi visualisasi pola aliran dua fase air-udara pada vertical upward circular mini-channel - Zulfikar Mahmud; Budi Santoso; Dominicus Danardono (Badan Kerja Sama Teknik Mesin Indonesia, 2018)
Two phases flow was important phenomenon in the industrial or engineering factories. Especially, the small or mini-channel was applied in the heat exchanger devices such as compact head exchanger and refrigeration evaporator/condenser. The circular transparent mini-channel with 2,5 mm and 5 mm inner diameters were used in this experiment. The flow pattern was identified. Bubble, slug, churn and annular were formed in vertical upward air-water flow. Bubbles flow pattern had elongated air-phase form with no aeration at the end air-phase. The flow pattern was plotted and analysed by flow pattern map in previous research. Actually, the new flow pattern map was reformed for 2,5 and 5 mm inner diameter pipe because of flow pattern map differences with the reference research. Both flow pattern maps had similarity form about mini-channel flow patern map.